2001
DOI: 10.1210/endo.142.1.8052
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic Acute Regulatory Protein and Peripheral-Type Benzodiazepine Receptor Associate at the Mitochondrial Membrane

Abstract: Steroidogenic acute regulatory protein (StAR) and peripheral-type benzodiazepine receptor (PBR) have both been implicated in the transport of cholesterol across mitochondrial membranes in steroidogenic cells. Therefore, we hypothesized that StAR and PBR were associated in this process. To test this hypothesis, we measured fluorescence energy transfer (FET) between these proteins by fusing enhanced green fluorescent protein (GFP, donor fluorophore) and yellow fluorescent protein (YFP, acceptor fluorophore) to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(40 citation statements)
references
References 0 publications
1
36
0
3
Order By: Relevance
“…Fifth, only limited domains of StAR, encompassing the C-helix and possibly the adjacent ⍀ loops, interact with lipid models of the OMM (15). Sixth, some data also implicate the peripheral benzodiazepine receptor (PBR), a small OMM protein, in the mitochondrial import of cholesterol (37), and recent data indicate that StAR interacts with PBR on the OMM to initiate cholesterol import (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, only limited domains of StAR, encompassing the C-helix and possibly the adjacent ⍀ loops, interact with lipid models of the OMM (15). Sixth, some data also implicate the peripheral benzodiazepine receptor (PBR), a small OMM protein, in the mitochondrial import of cholesterol (37), and recent data indicate that StAR interacts with PBR on the OMM to initiate cholesterol import (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence for the involvement of human peripheral benzodiazepine receptor (PBR) in steroidogenesis (26), and there are indications that StAR protein and PBR interact at mitochondrial membranes (27). This finding led to speculation about the possible involvement of an insect PBR in ecdysteroidogenesis (4).…”
Section: Discussionmentioning
confidence: 99%
“…Although a physical interaction between StAR and PBR/TSPO has not been established, FRET measurements indicated that StAR/StarD1 and PBR/TSPO come within the 100 A o of each other [89]. Moreover, Hauet et al [87] reported that isolated mitochondria from mouse Leydig MA-10 cells that express the Tom20/StAR fusion construct produce steroids at a maximal level, but if the cells are treated with PBRantisense oligonucleotides, their ability to synthesize the steroid is lost; on the contrary, re-introduction of recombinant PBR into the mitochondria in vitro rescued the steroidogenesis [87,90].…”
Section: Hormonal Regulation Of Steroidogenesismentioning
confidence: 99%